Drug treatment of pulmonary nontuberculous mycobacterial disease in HIV-negative patients: the evidence - van Ingen, Jakko; Ferro, Beatriz E; Hoefsloot, Wouter; Boeree, Martin J; van Soolingen, Dick (Expert review of anti-infective therapy, 2013)
Pulmonary disease (PD) caused by nontuberculous mycobacteria is an emerging infection mainly in countries where the incidence of tuberculosis is in decline. It affects an elderly population, often with underlying chronic lung diseases, but its epidemiology shows significant regional variation. Guidelines and recommendations for treatment of these infections exist, but build strongly on expert opinion, as very few good quality clinical trials have been performed in this field. Only for the most frequent causative agents, the Mycobacterium avium complex, Mycobacterium kansasii and Mycobacterium abscessus, a reasonable number of trials and case series is now available. For the less frequent causative agents of pulmonary nontuberculous mycobacterial (NTM) disease (Mycobacterium xenopi, Mycobacterium malmoense, Mycobacterium fortuitum, Mycobacterium chelonae) data is mostly limited to a few very small case series. Within this review, we have collected and combined evidence from all available trials and case series. From the data of these trials and case series, we reconstruct a more evidence-based overview of possible drug treatment regimens and their outcomes.